Pengembangan Augmented Reality Interaktif untuk Pengenalan Jajanan Tradisional Bali dengan Marker Based Tracking - Christina Purnama Yanti; Santi Ika Murpratiwi (Teknik Informatika Universitas Pamulang, 2021)
Augmented Reality is an IT technology that combines 2D or 3D virtual objects into a real environment and then projects these virtual objects in reality in real time. One way to use technology that researchers want to apply is to combine it with cultural products, namely traditional snacks. The increasing sources of information nowadays make modern snacks more popular than traditional foods. The author makes an application that can help introduce traditional snacks to the community. The method used to build the application is the Microsoft Solution Framework and Object Oriented Development methods. From the results of the research conducted, it can be concluded that the author succeeded in making an Augmented Reality Application Android for the introduction of traditional Balinese snacks using markers as media. The application is named ARjaje where the application can display 3-dimensional objects and use 2 buttons that can display information related to 3D objects in Indonesian or English. The application can display 14 types of traditional Balinese snacks and the application has been tested using the blackbox method.